Literary writing and ideological debate in Mahua literary magazines in the early period of cold war (1950-1969) - Lai, Mooi Heong (2019)
The Cold War refers to both regional and international political situation in the post-World War II which lasted for 46 years. It was a period of ideological confrontation and nuclear arms race between the Western and the Eastern Bloc, which leaded by the United States of America and the Soviet Union respectively. To prevent the spread of Communism in Southeast Asia, the Capitalist America extended their culture and promoted American values through foreign relation policies, funding and aids towards non-govermental organisations in Southeast Asia. This research aims to study the institutionalized of Mahua literary system under the influences of the Cold War during the 1950-60s. Through the publication of magazine, including the aim and manner of publishing, marketing and promoting strategies, issues of concern, this study intends to investigate how these publications were contained or restrained by the Cold War situation. The relation between politics and literature, especially the interaction and controversy between the realist and modernist writer will also be examined.